Enhancement of Biogas (Methane) Production from Cow Dung Using a Microbial Electrochemical Cell and Molecular Characterization of Isolated Methanogenic Bacteria - Bhatt, Puja; Poudyal, Pranita; Dhungana, Pradip; Prajapati, Bikram; Bajracharya, Suman; Yadav, Amar Prasad; Bhattarai, Tribikram; Sreerama, Lakshmaiah; Joshi, Jarina (Biomass (Basel, Switzerland), 2024)
Biogas has long been used as a household cooking fuel in many tropical counties, and it has the potential to be a significant energy source beyond household cooking fuel. In this study, we describe the use of low electrical energy input in an anaerobic digestion process using a microbial electrochemical cell (MEC) to promote methane content in biogas at 18, 28, and 37 °C. Although the maximum amount of biogas production was at 37 °C (25 cm3), biogas could be effectively produced at lower temperatures, i.e., 18 (13 cm3) and 28 °C (19 cm3), with an external 2 V power input. The biogas production of 13 cm3 obtained at 18 °C was ~65-fold higher than the biogas produced without an external power supply (0.2 cm3). This was further enhanced by 23% using carbon-nanotubes-treated (CNT) graphite electrodes. This suggests that the MEC can be operated at as low as 18 °C and still produce significant amounts of biogas. The share of CH4 in biogas produced in the controls was 30%, whereas the biogas produced in an MEC had 80% CH4. The MEC effectively reduced COD to 42%, whereas it consumed 98% of reducing sugars. Accordingly, it is a suitable method for waste/manure treatment. Molecular characterization using 16s rRNA sequencing confirmed the presence of methanogenic bacteria, viz., Serratia liquefaciens and Zoballella taiwanensis, in the inoculum used for the fermentation. Consistent with recent studies, we believe that electromethanogenesis will play a significant role in the production of value-added products and improve the management of waste by converting it to energy.